Pengembangan Media Praktikum PCT (Paper Chromatography Techniques) Berbasis Android dengan QR Code Technology pada Materi Pemisahan Campuran - Mellyta Uliyandari; Emilia Candrawati; Nurlia Latipah (PendIPA Journal of Science Education, 2022)
The purpose of this study was to develop an android-based PCT (Paper Chromatography Techniques) practicum media with QR code technology on mixed separation materials to help improve the quality of learning, especially in general chemistry practicum courses. This development is carried out using a 4D (four-D) research design, namely defining, designing, developing, and disseminating. At the definition stage, the formulation of the practicum objectives is carried out, the design stage is carried out by designing practicum media, while at the development stage the practicum media content validation is carried out by media experts and material experts, the dissemination stage is carried out through e-learning at Bengkulu University. The distribution of practicum media is carried out after the media is declared valid by the validator, namely material experts and media experts. The practicum media validation score by material experts is 70 which is in the "Eligible" category, while the validation results by media experts get 52 which is in the "Eligible" category. The results of the feasibility assessment of practicum media by students also showed results that were in the "appropriate" category with a conversion value of 31.93. Student responses to the PCT practicum media show an average score of 207.5 with a conversion value of 3.98 in the "agree" category. This can be interpreted that in general students agree with the aspects contained in the PCT practicum media so that the PCT media developed can be used in the learning process.